Maternal Parenting Practices in Feeding and Their Impact on Nutritional Status of Toddlers in Mampang Village, Depok City, West Java - Rahmi Nurmadinisia; Yulia Anggraeni Hidayat Putri; Priharyanti Wulandari; Ratna Mutu Manikam (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2025)
One indicator of community nutritional status is the nutritional status of children under five. Efforts to achieve good nutritional status for children under five cannot be separated from the role of parents, especially mothers, as caregivers because mothers are responsible for organizing family meals, including for children under five. Therefore, this study aims to assess the dominant risk factors related to maternal parenting in feeding with the nutritional status of toddlers. The research method used was an analytic observational study with a cross-sectional design. Data collection was conducted at the integrated health post (Posyandu) Mampang Village, Depok City, in May 2024, which coincided with the month of monitoring toddler growth and development. The population of this study was 1,853 toddlers. While the number of samples taken was 92 toddlers using the purposive sampling technique. The instrument used was a maternal parenting questionnaire modified from the Ministry of Health’s infant and young child feeding guidelines, and the reliability test results of this questionnaire were 0.722. Data analysis used the chi-square test, and multivariate analysis used the logistic regression risk factor model. The results showed that 87% of toddlers had good nutritional status and 13% were malnourished. Based on the study result, the factor that plays the most role in the nutritional status of toddlers is the provision of main meals 3 times (p-value 0.000) and snacks 2 times a day (p-value 0.046). Training in feeding the type and amount, how to serve, and variety of food diversity is necessary to improve toddlers’ optimal growth and development.